ANALISIS KINERJA SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN - Septimus Mali; Stanis Manafe (Ma Chung Press, 2017)
This research aimed at knowing the description of liquidity factors (current ratio, cash ratio dan quick ratio), solvability (debt to equity ratio, debt to asset ratio dan long term debt to equity ratio), remunirativeness (earning power) and share performance (share price) of manufacture enterprise, automotive and component sub-sector in Year 2010-2015, and the impact of the change in liquidity ratio, solvability, and remunerativeness to the enterprise’s share performance (share price). The results of this study showed that liquidity ratio consisting of current ratio, cash ratio, dan quick ratio was less liquid, solvability ratio consisting of debt to equity ratio, debt to asset ratio and long term debt to equity ratio was solvable enough, and remunerativeness ratio (earning power) decreased in each period. The value raise of current ratio, cash ratio and quick ratio and earning power tended to be followed by the raise of share performance (share price) of the enterprise. If the current ratio, cash ratio, quick ratio and earning power decreased, the share performance (share price) tended to decrease. The value increase of debt to equity ratio, debt to asset ratio and long term debt to equity ratio tended to decrease share performance (share price), while the low solvability value will increase share performance (share price).